2006
DOI: 10.1056/nejmoa051285
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Entecavir and Lamivudine for HBeAg-Positive Chronic Hepatitis B

Abstract: Among patients with HBeAg-positive chronic hepatitis B, the rates of histologic, virologic, and biochemical improvement are significantly higher with entecavir than with lamivudine. The safety profile of the two agents is similar, and there is no evidence of viral resistance to entecavir. (ClinicalTrials.gov number, NCT00035633.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

68
982
11
34

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,325 publications
(1,105 citation statements)
references
References 27 publications
68
982
11
34
Order By: Relevance
“…Entecavir is a guanosine nucleoside analog that has demonstrated efficacy against nucleoside-naive and lamivudine-refractory CHB [26][27][28][29]. In global clinical studies, patients with lamivudine-refractory CHB treated with entecavir 1 mg daily for 48 weeks experienced reduction in HBV DNA levels of more than 5 log copies/mL and improvements in hepatic necroinflammation and fibrosis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Entecavir is a guanosine nucleoside analog that has demonstrated efficacy against nucleoside-naive and lamivudine-refractory CHB [26][27][28][29]. In global clinical studies, patients with lamivudine-refractory CHB treated with entecavir 1 mg daily for 48 weeks experienced reduction in HBV DNA levels of more than 5 log copies/mL and improvements in hepatic necroinflammation and fibrosis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The model for end-stage liver disease (MELD) score was calculated using serum creatinine, bilirubin, and INR of prothrombin time 11 according to the following formula: 9.57 Â Ln (creatinine mg/dL) þ 3.78 Â Ln (bilirubin mg/dL) þ 11.20 Â Ln INR þ 6.43. 24 Radiologic cirrhosis was defined as coarse liver echotexture with nodularity and small liver size or the presence of features of portal hypertension (e.g., ascites, splenomegaly, and varices) noted on liver imaging.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Entecavir is a more potent antiviral agent than lamivudine and adefovir. [11][12][13] Most entecavir-treated patients achieve maintained viral suppression and low Abbreviations: ALT, alanine aminotransferase; anti-HBe, antibody against hepatitis B e antigen; CHB, chronic hepatitis B; CI, confidence interval; HBeAg, hepatitis B e antigen; HBsAg, hepatitis B surface antigen; HBV, hepatitis B virus; HCC, hepatocellular carcinoma; HR, hazard ratio; INR, international normalized ratio; MELD, model for end-stage liver disease; SBP, spontaneous bacterial peritonitis.…”
mentioning
confidence: 99%
“…Two phase III pivotal trials of entecavir 0.5 mg daily versus lamivudine 100 mg daily in 715 HBeAg-positive patients and 648 HBeAg-negative patients have shown that entecavir is superior to lamivudine at week 48 of treatment [15,16]. Entecavir has also been found to be superior to 10 mg of adefovir at week 48 of treatment in an open-label study of 69 treatment-naive, HBeAg-positive patients [17].…”
mentioning
confidence: 99%
“…A phase III, double-blind control trial in 286 lamivudinerefractory, HBeAg-positive patients showed that switching to entecavir (141 patients) with a 1 mg daily dose (twice the dose for nucleoside-naive patients) provided better histologic improvement, HBV DNA reduction, and ALT normalization than continuing lamivudine at week 48 [24]. However, the reduction of HBV DNA was less than in nucleoside-naive patients; only 19% of lamivudine-refractory patients having HBV DNA of \300 copies/mL (*60 IU/mL) compared with the 67% of nucleoside-naive patients [15]. By week 48, 1.4% of patients had virologic rebound due to the emergence of entecavir-resistant mutants, with seven other patients (of 134 tested) identified to have entecavir-resistant mutants at baseline without virologic rebound.…”
mentioning
confidence: 99%